Equidade de gênero na ciência? Um estudo sobre as pesquisadoras bolsistas de produtividade da Universidade Federal de São Carlos - Carvalho, Carolina Cisoto Barbosa de (2016)
The woman´s access to higher education and academic career is na achievement. More and more women occupy the graduation chairs, getting to many areas of knowledge, occupying more than half of the places offered. But the number of women found in the highest scientific career positions remains low. What happened along this career path that prevents women able to ascend vertically? The glass ceiling assumption seems to define the force that keeps women in lower hierarchical positions. The glass ceiling is formed not by one, but by many barriers and obstacles that add up acting often in the loss of women throughout their careers. This work seeks to understand a little of the professional lives of researches who managed to get to a privileged elite of science, the "National Counsel of Technological and Scientific Development" – CNPq grant recipients in research, with the intention to diagnose the nature and impact of gender differences throughout the scientific career. From this point is possible to draw up suggestions for actions that seek to provide an institutional environment with equal opportunities for both genders.